Icelandic NGOs and Humanitarian Aid: A Look at the Allocation Process - Þorsteinn Valdimarsson 1989- (2015)
Icelandic NGOs have increasingly engaged in humanitarian assistance in recent years with the support of The Ministry of Foreign Affairs (MFA), which announces funds for non-governmental organisations (NGOs) in humanitarian aid biannually, and additionally in case of severe disasters. The aim of this research is to pry into the decision making process of five Icelandic NGOs when applying for such funds and the ethical implications of those decisions. The NGOs are The Red Cross, The Church Aid, SOS Children’s Villages, Save the Children and ABC Children’s Aid. Explored are the NGOs’ connections with INGOs, their Codes of Conduct, their relations with the MFA and the factors that influence their selection of projects. The research is primarily based on interviews with NGO employees. While there is much variety in the NGOs practices, they have a common ambition for the advancement of their humanitarian efforts. The NGOs appear prone to apply for funds if emergencies occur close to their own projects, are in the MFAs focus areas, are emphasised by their INGO contacts, are considered extensive by the NGOs and if they believe their expertise is of use. All interviewees agreed that the allocation system of the MFA should be improved, and believed that professionalism could be increased with steadier funding. Keywords: Development studies, humanitarian aid, NGOs, Iceland, allocation, ethics, the Ministry of Foreign Affairs (MFA) Íslensk borgarasamtök hafa undanfarin ár aukið umsvif sín í veitingu mannúðaraðstoðar með stuðningi Utanríkisráðuneytisins. Ráðuneytið auglýsir eftir umsóknum borgarasamtaka um mannúðaraðstoð tvisvar á ári og aukalega í tilfelli alvarlegra hamfara. Rannsókn þessi miðar að því að skyggnast inn í ákvarðanatökuferli fimm helstu borgarasamtaka þegar kemur að umsóknum um slíka styrki og siðferðilegar hliðar þeirra ákvarðanna. Samtökin eru Rauði krossinn, Hjálparstarf kirkjunnar, SOS barnaþorp, Barnaheill og ABC barnahjálp. Skoðuð eru samskipti félaganna við erlend móður- eða regnhlífasamtök, ...